PROSES PENCIPTAAN PANTUN DAN TALIBUN DALAM KABAURANG PIAMAN DAN IMPLIKASINYA DALAM PEMBELAJARAN APRESIASI SASTRA - Refisa Ananda; Najmi Hayati (STKIP Pesisir Selatan, 2020)
This study aims to describe the process of creating pantun and talibun in kaba Urang Piaman at the Dendang Pauah performance and its implications for learning literary appreciation in high schools.This research is a qualitative research with descriptive analysis method. Data collection techniques used in this study were interviews, recordings, direct observation, and field notes. Participants in this study were dendangers (Tasar), saluang artisans (Pono), and people in Koto Lalang Village, Lubuk Kilangan District, Padang City. The results of the data analysis show that the creation of the pantun and talibun in the Urang Piaman kaba at the Dendang Pauah performance is carried out by remembering techniques. The memory technique allows the drummer to improvise during the performance. The structure of the kaba text is in the form of narrative poetry and lyrical prose which uses poetry elements in the form of rhymes and talibun following a certain formula. The formula is applied to each line of text throughout the show. The formulas are at the couplet level, line pairs, single line, and more on the line (phrases, clauses, and words).